Impacts of Frailty on Prognosis in Lung Cancer Patients: A Systematic Review and Meta-Analysis - Dai, Shuiping; Yang, Ming; Song, Juan; Dai, Sisi; Wu, Jinhui (Frontiers in Medicine, 2021)
Background: Frailty is a common geriatric syndrome and is described as a limited ability to compensate and recover from stressors. Lung cancer is largely diagnosed in old age, when frailty is common and might have predictive value on prognosis. Therefore, we performed a systematic review to evaluate the prognostic role of frailty in lung cancer. Methods: The online PubMed, Web of Science, CNKI and Wanfang literature databases were searched to identify all related articles that reported the predictive value of frailty for mortality and therapeutic toxicity. Review Manager 5.3 was used to analyze results by standard meta-analysis methodology. Results: Seven studies with 3921 lung cancer patients enrolled in this review. Patients in two studies received chemotherapy, two studies radiotherapy, two studies surgery, one study not reported. Compared to non-frail patients, frail patients had a higher risk of overall mortality (Hazard Ratio (HR) = 1.57, 95% confidence interval (CI), 1.32-1.87), and therapeutic toxicity (Odds Ratio (OR) = 2.60, 95% CI, 0.82-8.24). Prefrail patients also showed higher overall mortality and therapeutic toxicity than non-frail patients (HR = 1.20, 95% CI, 1.05-1.38; OR = 1.72, 95% CI, 1.18-2.51, respectively). Conclusions: Frailty is a powerful predictor of overall mortality and therapeutic toxicity in lung cancer patients.